ANALISIS WAKTU DELAY PENGIRIMAN PAKET DATA MENGGUNAKAN JARINGAN WIFI PADA INVENTARISASI BARANG BERBASIS APLIKASI ANDROID - Kurnianto, Danny; Danisyah, Achmad Rizal; Muhdori, Miftahul (Proceeding SENDI_U, 2015)
It takes a long time to process inventory items are done manually using an inventory form before entered on thecomputer database. Using the android-based application on a smartphone as a replacement for an inventory form,then the inventory to be faster because reading or inputting data on a computer database can be done directlythrough the app android by utilizing the Wi-Fi network using client-server concept. Computer as a server thatprovide special services to the client (android application on the smartphone) that store and read the data if requiredby the client. The protocol used in data communication between a server computer with android application is TCPand HTTP protocol with a static IP address. Analysis of data packet transmission is done using Wireshark softwareand parameters measured were the flow of data packets and time delay. The test results on the time delay of the datadelivery show that greater the distance between the access point and client (android), the time delay of datatransmission will be greater with an average value of 14 ms. The time required to complete all inventory processusing android application on the smartphone at 7 minutes 45 seconds. whereas if inventory is done manually takestime for 21 minutes 64 seconds.Keyword : Data packets transmission, time delay, Wi-Fi, android, client-server